Engagement With Reservation-Based Head Start Teachers to Explore Their Stress and Coping: A Qualitative Study - Wilson, Deborah; Sarche, Michelle; Ricker, Adriann; Krienke, Lydia Koh; Brockie, Teresa (Elsevier, 2024)
Native Americans residing in remote reservation communities find strength in connection to place, culture, language, and sovereignty; they also face challenges as their communities struggle with historical and contemporary traumas that have resulted in poverty, high crime and suicide rates and drug misuse. The psychological well-being of Head Start teachers who teach and support the needs of Native American children, is overlooked. Methods Qualitative interviews (n = 18) and focus groups (n = 9) were conducted with Head Start teachers, supervisors, parents, and ancillary staff to identify risk and protective factors at each level of the socioecological model (individual, relationships, community, society). Using content analysis and F4 analyse software two coders identified recurring themes. Results Individually teachers are resilient, focused more on the children's well-being than their own. Family was both significant support and stressor. Community struggles with drug and alcohol misuse and homelessness were the most frequent stressors. Workplace support included their supervisors and the mentorship they provided each other. Spirituality in the form traditional cultural practices, prayer and Christen faith were important sources of support and well-being. Conclusions This paper provides insight into the stress and coping mechanisms of reservation-based Head Start teachers, identifying ways to protect and promote their health and well-being. It is important to provide support at all levels of the socioecological model to enable these teachers to strengthen their physical and psychological health and wellbeing so that they may support the children and families of Head Start to help strengthen Native American health overall.
Keywords: 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; Nursing; 4205 Nursing